EFEKTIVITAS PEMBELAJARAN BAHASA INGGRIS PADA MAHASISWA STAB MAITREYAWIRA PEKANBARU - Wira Jaya Hartono (JGK (Jurnal Guru Kita), 2022)
The Effectiveness of English Learning To Students of Stab Maitreyawira Pekanbaru. The purpose of this study is to describe the effectiveness of ENglish Learning in Maitreyawira STAB students in Pekanbaru. This is a qualitative research. It described the learning achievement process based on: 1) lecturer’s ability; 2) students activity; 3) result (individual and group). The result of this study were: 1) the process of English Learning in Maitreyawira STAB students ran well. The lecturer interesting approach in learning process and students were active; 2) the whole English Learning process was good since it was made based on RPS and the students were active and gave positive response; 3) the evaluation  was in normal category since the IPK was 75 which meant the learning process was ‘normal’